Hooded Grebe Podiceps gallardoi population decreased by eighty per cent in the last twenty-five years - Roesler, Carlos Ignacio (2012)
We estimated the present population size of the Hooded Grebe Podiceps gallardoi and compared it with the population in 1985. During the breeding seasons 2009/2010 and 2010/2011 we monitored 251 lakes on the main plateaus of Santa Cruz province, southern Patagonia, Argentina, where the entire population of Hooded Grebes spends the breeding season. During 2009/2010 we monitored 131 lakes and observed 521 Hooded Grebes in 16 lakes, while during 2010/2011 we monitored 186 lakes and observed 535 individuals in 14 lakes. At both breeding seasons five lakes contained near 85% of the population. We only observed 6 breeding colonies, two in 2009/2010 and four in 2010/2011, totalling 242 nesting attempts. Nearly 90% of the nests failed during egg stage, mainly due to strong winds and depredation by American mink Neovison vison. Only 28 nests hatched chicks, but none of the young survived to independence due to low temperatures. We compared the results of our 2010/2011 survey with one conducted during 1984/1985 and detected that the population diminished by approximately 80%. This decline was observed on all but one plateau (Buenos Airesa) where most breeding attempts occurred. Our results show that at present Hooded Grebes are highly dependent on a few suitable lakes where they congregate to breed. We analyse possible causes for the decline of the population and propose conservation actions to protect this species.